The Development of Music for Tai Loei Morlum - laokhonka, Phongphat; Khumkhet, Sarinthorn; Phimnon, Suphawut (Journal of Fine and Applied Arts Khon Kaen University, 2024)
This research focuses on developing musical accompaniment for Morlam Tai Loei performances to enhance and innovate the music used in these traditional art forms. Using observational techniques and structured interviews, the study employs descriptive and analytical methods to analyze the music. The results reveal two primary categories of musical compositions: traditional and newly composed pieces. The traditional group includes four compositions adhering to Thai classical and Isan folk music conventions: Homrong Morlam Tai Loei, Phaya Dern, Nang Nak, and Sut Sanehan. The newly composed group features innovative pieces that reflect the performers’ actions and emotions, incorporating Western musical techniques into Isan folk elements: Love, Surprise, Grandeur, and Faith. The accompaniment is performed by a modernized Isan folk ensemble blending traditional and contemporary practices. This study contributes to ethnomusicology by demonstrating the integration of traditional and contemporary musical elements, thereby preserving and evolving Morlam Tai Loei within contemporary artistic contexts.